Aplikasi Kombinasi Pupuk Kiserite dan Pupuk NPK Terhadap Nisbah Dispersi Tanah Pada Pertanaman Jagung (Zea mays L.), Bandar Lampung: Application Combination Of Kieserite and NPK Fertilizers on Soil Dispersion Ratio In Maize (Zea Mays L.), Bandar Lampung - Ramadhani, Winih Sekaringtyas; Faqina, Sadila; Afandi; Septiana, Liska Mutiara; Novpriansyah, Hery (Agrocentrum, 2025)
Changes in corn production are related to the decline in agricultural land quality. One of the main indicators for assessing soil aggregate stability is the dispersion ratio. The efforts made in this study were the application of Kieserite and NPK fertilizers. This study aimed to determine the effect of the combination of Kieserite and NP K fertilizers on the soil dispersion ratio in corn crops, as well as to determine the best combination dose. The study was conducted in Campang Raya, Bandar Lampung from August 2024–May 2025 using a Randomized Block Design (RAK) with four treatments and six replications, namely A = Control, B = Standard Fertilizer (NPK), C = 1 Kieserite + 1 NPK, and D = 1 Kieserite + ¾ NPK. The main parameter was the soil dispersion ratio, with supporting parameters in the form of microaggregate distribution, soil texture, pseudo sand, soil pH, and corn production. The results showed that all treatments still produced the "highly dispersed" category (65.83–73.42%), with the lowest value in treatment C and the highest in the control. Combination of Kieserite + NPK application did not significantly improve the dispersion ratio or microaggregate distribution, but did affect corn production. Treatment C resulted in dry corn kernel production of 2.37 tons ha⁻¹, higher than the control at 1.47 tons ha⁻¹. This increase in corn production is supported by the role of Mg²⁺ ions from kieserite which can improve photosynthesis efficiency, chlorophyll formation, and transport of photosynthesis products to the cob. Magnesium fertilization in the soil plays an important role in stimulating plant metabolism, improving the quality and quantity of harvests, and the supply of NPK nutrients that stimulate root growth and root exudates to aid aggregation.